2007
DOI: 10.1093/eurheartj/ehm393
|View full text |Cite
|
Sign up to set email alerts
|

Low-gradient aortic stenosis: impact of prosthesis-patient mismatch on survival

Abstract: Outcomes after surgery for low-gradient AS were prospectively assessed in 152 consecutive patients from seven institutions. There were 113 men (74%); mean age was 72 years (64-76); valve area, 0.7 cm(2) (0.6-0.8); left ventricular (LV) ejection fraction 0.31 (0.25-0.37) and baseline mean transaortic pressure gradient (MPG), 30 mmHg (25-35) Among 139 patients with available prosthetic valve effective orifice area (EOA), PPM (defined by an indexed EOA < or = 0.85 cm(2)/m(2)) was present in 79 patients (57%) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0
2

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 37 publications
1
28
0
2
Order By: Relevance
“…Differences in age distribution, prevalence of obesity, and prevalence of moderate versus severe PPM in the patient populations may also help explain the discrepancies observed among previous studies. To this effect, studies conducted in younger patient populations (3,25) generally found that PPM has a significant impact on late survival; studies in elderly populations (11,12) often failed to demonstrate any significant association. Interaction between PPM and age.…”
Section: Discussionmentioning
confidence: 99%
“…Differences in age distribution, prevalence of obesity, and prevalence of moderate versus severe PPM in the patient populations may also help explain the discrepancies observed among previous studies. To this effect, studies conducted in younger patient populations (3,25) generally found that PPM has a significant impact on late survival; studies in elderly populations (11,12) often failed to demonstrate any significant association. Interaction between PPM and age.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, while some researchers have defended the hypothesis that PPM affect survival and/or functional class [15,16], others consider it a phenomenon with no clinical importance or that only affects the prognosis in young patients and in patients of any age with ventricular dysfunction [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…Gray's piecewise-constant time-varying coefficients survival model is an extension of the Cox proportional hazards model that allows the regression coefficients to change over different time intervals (16). It has, therefore, the ability to estimate how the hazards of individual risk factors change over time (6,16) and may be better suited for modeling survival after cardiac surgery. We used single-variable Gray models to identify variables associated with 5-year overall mortality.…”
Section: Methodsmentioning
confidence: 99%